2021
DOI: 10.25100/cm.v52i2.4801
|View full text |Cite
|
Sign up to set email alerts
|

Damage control in the emergency department, a bridge to life

Abstract: Patients with hemodynamic instability have a sustained systolic blood pressure less or equal to 90 mmHg, a heart rate greater or equal to 120 beats per minute and an acute compromise of the ventilation/oxygenation ratio and/or an altered state of consciousness upon admission. These patients have higher mortality rates due to massive hemorrhage, airway injury and/or impaired ventilation. Damage control resuscitation is a systematic approach that aims to limit physiologic deterioration through a group of strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, REBOA could be a bridge between hemodynamic support and final hemorrhage control. 9,32,40,41 This strategy must rely on ongoing endovascular skills training and the formation of a multidisciplinary team with a well-trained trauma surgeon at its head. [41][42][43]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, REBOA could be a bridge between hemodynamic support and final hemorrhage control. 9,32,40,41 This strategy must rely on ongoing endovascular skills training and the formation of a multidisciplinary team with a well-trained trauma surgeon at its head. [41][42][43]…”
Section: Discussionmentioning
confidence: 99%
“…The intervention of emergency trauma patients in MDT mode and damage control surgery when necessary can significantly reduce the mortality rate and improve the prognosis of patients. [ 20 ] As a basic treatment model for modern diseases, MDT is conducive to the development of a multidisciplinary mindset, and trainees can integrate theoretical medical knowledge and clinical specialty practice by participating in the treatment process of emergency trauma patients. [ 21 , 22 ] In our teaching study, we found that both groups of trainees had significantly improved their assessment scores after participating in the MDT model of emergency trauma teaching, suggesting that this method is practical and feasible to be applied to the training teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding is the main cause of death. The management of the severely injured trauma patient in the emergency department requires a multidisciplinary team that performs damage control maneuvers aimed at rapidly controlling bleeding, hemostatic resuscitation, and/or prompt transfer to the operating room, if required [ 22 ]. Therapeutic tactics for “damage control” are divided into three phases [ 7 ].…”
Section: Special and Non-specialized Diagnostic Methodsmentioning
confidence: 99%